Hubungan kelekatan terhadap ibu dan penyesuaian diri pada remaja disabilitas fisik - Azza Febria Nuraini (Cognicia, 2020)
As social beings, adolescent with physical disability are required to interact with their social environment to fulfillment and achieve inner tranquility with its surroundings. Limitations in adolescent with physical disability often make them feel inferior, especially if the response in the environment does not accept their physical condition, it will causes psychological problems and make adolescent with physical disability tend to withdraw from social environment. Adolescent attachment to the mother is predicted to increase self-esteem and become resilience in adolescent with physical disability. The purpose of this study to determine the relationship of attachment to the mother and adjustment in adolescent with physical disability. This research is a correlational quantitative research with sample of 56 adolescent with physical disability aged 12-21 years old. Methods of data collection using total sampling technique with adolescent attachment scale to mother and adjustment and analyzed using product moment pearson correlation. This study shows (r = 0.815, p = 0,000). Thus, it can be concluded that there is a significant positive relationship between attachment to the mother and adjustment in adolescent with physical disability.